Serous atrophy of bone marrow: a rare cause of paediatriccytopenia - RUCHEE KHANNA; SEEMITR VERMA; VARUN KUMAR SINGH; SUSHMA BELURKAR (International Journal of Pharma and Bio Sciences, 2017)
Serous atrophy of bone marrow also known as gelatinous transformation or serous fat atrophy is a rare finding. It is characterised by focal loss of hematopoietic elements, fat cell atrophy, and extracellular deposition of gelatinous substance with adjacent marrow hypoplasia. Pathogenesis of such atrophy is poorly understood and is considered to be a non specific finding, which can be associated with various haematological and non haematological conditions. It is mostly seen in adults with a few cases reported in the paediatric age group. We present a case of an 8 year old female patient with bilateral knee joint pains since one year. Blood counts and peripheral smear examination revealed bicytopenia (anemia and thrombocytopenia) along with a low normal total leucocyte count and a low reticulocyte count. Bone marrow aspirate consisted predominantly of sinusoidal blood and hence was inconclusive. Bone marrow biopsy from the iliac crest of right and left sides showed hypocellular marrow spaces with deposition of extracellular pink amorphous material suggestive of serous atrophy. Alcian blue at a pH of 2.5 was done to confirm the diagnosis and it stained the deposits blue. Therefore a diagnosis of hypoplastic bone marrow with associated serous atrophy was made. Bone marrow study is a vital tool in evaluation of cytopenias in pediatric age group as it helps to narrow down the list of differential diagnosis. In case of extracellular eosinophilic deposits with marrow hypoplasia, a differential of serous atrophy should be borne in mind.